First love - Riley, Gwendoline, 1979- (New York Review Books classics., 2022)
"Catastrophically ill-suited for each other, and forever straddling a line between relative calm and explosive confrontation, Neve and her husband, Edwyn, live together in London. For the moment, they have reached a place of peace in their relationship, but past battles have left scars. As Neve recalls the decisions that brought her to Edwyn, she describes other loves and other debts- from her bullying father and her self-involved mother, to a musician she struggled to forget. Drawing us into the battleground of this marriage, Gwendoline Riley tells a transfixing story of mistakes and misalliances, of helplessness and hostility, in which both husband and wife have played a part. Could this possibly be, nonetheless, a story of love?"--